Pi’s Anxiety in Yann Martel’s Life of Pi - Feni Asniar; Anik Cahyaning Rahayu (CV Wahana Publikasi, 2024)
This research aims to describe the symptoms, causes, effects, and types of Pi’s anxiety. The approach used in this study is the extrinsic approach, in this case, the psychological approach, because anxiety is one of the psychological problems. Sigmund Freud’s psychoanalytic theory is used to analyze Pi’s anxiety. This research uses a qualitative research method. The qualitative method collects the necessary data from the novel to achieve the research objective and references relating to the topic to support the analysis. Symptoms of anxiety experienced by Pi are feeling anxious, being unable to think of anything except something that makes him anxious, and experiencing the deepest tremors, pain, and sadness. There are several reasons for Pi’s anxiety. The first is a ship accident caused by a big storm that hits the ship he travels with his family. The second cause is meeting a tiger. The third cause is worrying about his safety. The conclusion is that Pi suffers from anxiety because of his uncontrollable emotions and worry. Sinking ship, encountering tigers, and becoming worried about his safety are the causes of his anxiety. He also feels behavioural, emotional, and cognitive effects. Pi suffers from a neurotic and objective type of anxiety reflected in its symptoms, causes, and effects.